Mapping public debates about the climate security-human mobility nexus in Jordan: A social media analysis - Carneiro, Bia; Tucci, Giulia; Gomes, Frederico; Cruciata, Pietro; Resce, Giuliano (2023)
This working paper uses an online issue mapping approach to explore two research questions: 1) How is human mobility in Jordan represented in local and international social media conversations? 2) What associations between human mobility and climate security-related topics are present in these public debates? Overall, results show diverging agendas between national and international actors, as well as a low prevalence of climate and security related topics, both in terms of absolute frequencies and in relation to the content that garnered most attention in conversations.